Дослідження процесу очищення води цементацією від міді в статичних умова, в процесі її відновлення на частинках залізного порошку - Зоря, Д. І. (Ways to Improve Construction Efficiency, 2012)
Presented results of studies for effect of cooper containing wastewater treatment by cementation. Was investigated kinetics of copper ions’ content in solution at it’s cementation on iron powder.